2016
DOI: 10.1016/j.jpowsour.2015.10.034
|View full text |Cite
|
Sign up to set email alerts
|

A flexible all-inorganic fuel cell membrane with conductivity above Nafion, and durable operation at 150 °C

Abstract: The search for fuel cell membranes has focused on carbon backbone polymers, among which Nafion seems to best survive the most severe of the degradation mechanismsattack by peroxide radicals. Less attention has been given to inorganic membranes because of their generally inflexible nature and lower conductivity, though some SiO 2-Nafion composites have shown improved properties. Nafion dominates, despite needing hydration, which then restricts operation to below 100ºC (so CO poisoning problems persist). Describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
(53 reference statements)
1
26
0
Order By: Relevance
“…They attributed the reasons to the enhanced PA adsorbing ability of membranes through electrostatic interactions. Meanwhile, Aili et al and Angell and co‐workers recently found that silicon oxides could improve the acid retention of membranes due to the formation of phosphosilicates. On the other hand, the introduced siloxane network might cause a separation of polymer backbones and created a more free volume for adopting phosphoric acid, which resulted in much more phosphoric acid uptake.…”
Section: Resultsmentioning
confidence: 99%
“…They attributed the reasons to the enhanced PA adsorbing ability of membranes through electrostatic interactions. Meanwhile, Aili et al and Angell and co‐workers recently found that silicon oxides could improve the acid retention of membranes due to the formation of phosphosilicates. On the other hand, the introduced siloxane network might cause a separation of polymer backbones and created a more free volume for adopting phosphoric acid, which resulted in much more phosphoric acid uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical stability and thermal stability of the s -PI-PVDF composite membranes were subsequently analyzed for the consideration of long-term application in DMFC [50]. The mechanical strengths of the composite membranes are shown in Figure 7a.…”
Section: Resultsmentioning
confidence: 99%
“…Strong mechanical property of the membrane is one of the important demands to withstand high compression for MEA fabrication of PEMFC and DMFC applications [ 37 ]. The hybrid membranes exhibited good mechanical property from the stress-strain plots, as shown as displayed in Figure 6 a.…”
Section: Resultsmentioning
confidence: 99%